2019
DOI: 10.1101/612911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High specificity of widely used phospho-tau antibodies validated using a quantitative whole-cell based assay

Abstract: List of abbreviationsAD: Alzheimer's disease; HEK: Human embryonic kidney; phospho-tau: phosphorylated tau; PHF: paired helical filament; EGFP: enhanced green fluorescent protein; iRFP: infrared fluorescent protein; λ P P : lambda protein phosphatase; WT: wild-type; GSK-3β: PTM: post-translational modification; glycogen synthase kinase-3β; scFv: single-chain antibody variable fragment; pThr231: phospho-threonine 231, RRID: Research Resource Identifier. AbstractAntibodies raised against defined phosphorylation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…A report using Western blot to evaluate the specificity of various pTau antibodies noted that AT8 showed a relatively high level of nonspecificity in their assay, whereas PHF1 and CP13 showed high specificity (60). Another recent study using a different assay (flow cytometry in an HEK binding assay) found that AT8 and PHF1 showed highly specific binding (61). These findings may help to explain the different patterns observed immunohistochemically with different pTau antibodies.…”
Section: Changes In Taumentioning
confidence: 95%
“…A report using Western blot to evaluate the specificity of various pTau antibodies noted that AT8 showed a relatively high level of nonspecificity in their assay, whereas PHF1 and CP13 showed high specificity (60). Another recent study using a different assay (flow cytometry in an HEK binding assay) found that AT8 and PHF1 showed highly specific binding (61). These findings may help to explain the different patterns observed immunohistochemically with different pTau antibodies.…”
Section: Changes In Taumentioning
confidence: 95%
“…However, the nature of tau present within these aggregates is unclear. In order to investigate the phosphorylation state of tau within these aggregate species, we performed twocolor SMLM using two commonly used phospho-tau antibodies, Thr231 and AT8, which are known to have high labeling specificity (32). Thr231 targets tau that is phosphorylated at the 231st threonine, which is considered to be an early marker of tau aggregation.…”
Section: Phosphorylation Of Specific Tau Residues Is Associated With Differentmentioning
confidence: 99%
“…We isolated primary cortical neurons from embryonic mice (E15‐16) and starved them for 7 DIV to investigate P‐tau's pathogenic intraneuronal spread (Figures 1 and S1). Then, we examined the formation and localization of cis P‐tau (early driver), AT8 P‐tau (early tangle), and AT100 P‐tau (late tangle) (Li & Cho, 2020) at various time points. Following starvation, we observed significant intraneuronal spread of P‐tau markers.…”
Section: Resultsmentioning
confidence: 99%